Egg and Dietary Cholesterol Intake and Risk of All-Cause, Cardiovascular, and Cancer Mortality: A Systematic Review and Dose-Response Meta-Analysis of Prospective Cohort Studies - Darooghegi Mofrad, Manije; Naghshi, Sina; Lotfi, Keyhan; Beyene, Joseph; Hypponen, Elina; Pirouzi, Aliyar; Sadeghi, Omid (Frontiers in Nutrition, 2022)
Objective: This systematic review and meta-analysis of prospective cohort studies examined the associations between egg and dietary cholesterol intake and the risk of mortality from all causes, cardiovascular disease (CVD) and cancer. Methods: PubMed, Scopus, ISI Web of Knowledge, and Google Scholar until April 2021 and references of retrieved relevant articles. Random-effects models were used to calculate summary relative risk (RR) and 95% confidence intervals (CI) for the highest versus lowest categories of egg and dietary cholesterol intake. Also, linear and non-linear dose-response analyses were conducted to examine the dose-response relationships. Results: We included 55 studies, comprising data from 2,772,486 individuals with 228,425, 71,745, and 67,211 cases of all-cause, CVD, and cancer mortality, respectively. Intake of each additional egg per day was associated with a 7% higher risk of all-cause (1.07, 95% CI: 1.02 to 1.12, I2 = 84.8%) and a 13% higher risk of cancer mortality (1.13, 95% CI: 1.06 to 1.20, I2 = 54.2%), but was not associate with CVD mortality (1.00, 95% CI: 0.92 to 1.09, I2=81.5%). Non-linear analyses showed elevated risks for intake above 1.5 and 0.5 eggs/day, respectively. Each 100 mg/day increment in dietary cholesterol intake was associated with a 6% higher risk of all-cause mortality (1.06, 95% CI: 1.03 to 1.08, I2=34.5 %) and a 6% higher risk of cancer mortality (1.06, 95% CI: 1.05 to 1.07, I2=0 %), but was not associated with CVD mortality (1.04, 95% CI: 0.99 to 1.10, I2=85.9 %). Non-linear analyses demonstrated risks elevating above 450 and 250 mg/day, respectively. Conclusions and Relevance: High dietary intake of eggs and cholesterol was associated with all cause and cancer mortality. Little evidence for elevated risks were seen for intakes below 0.5 egg/day or 250 mg/d of dietary cholesterol. Our findings should be considered with caution because of small risk estimates and moderate between-study heterogeneity.